KEADILAN SOSIAL DAN PASAL 33 UUD PASCA AMANDEMEN: ANALISIS AKTIVITAS EKSTRAKTIVISME DI INDONESIA - Ayusia Sabhita Kusuma (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2026)
ABSTRACT This study analyzes the implementation and normative substance of the social justice values enshrined in Article 33 of the 1945 Constitution within the context of extractivist activities in Indonesia. Through a literature review and policy analysis, the study evaluates whether current natural resource governance remains aligned with the spirit of paragraph (3), namely, the greatest prosperity of the people, or has instead become entrenched in oligarchic interests. Employing John Rawls’s Justice as Fairness framework alongside the concept of Pancasila Social Justice, the research identifies a paradox between post-amendment regulations to Article 33 that emphasize market efficiency and the ideal of a familial (communitarian) economy. The analysis shows that corporate dominance in extractivism activities triggered massive deforestation, exacerbating ecological disasters such as floods and landslides in Sumatra. This indicates violations of distributive, commutative, and legal justice, whereby the burdens of environmental degradation are borne by vulnerable communities while economic benefits are concentrated among a small elite. In conclusion, the post-amendment Article 33 strengthens state control through the centralization of licensing, expands corporate dominance, and increases public losses, thereby further distancing the implementation of Article 33 from the principles of substantive social justice. Keywords: Extractivism, Social Justice, Pancasila, Article 33, justice theory ABSTRAK Penelitian ini menganalisis implementasi dan substansi normatif nilai keadilan sosial Pasal 33 UUD 1945 dalam konteks aktivitas ekstraktivisme di Indonesia. Melalui tinjauan literatur dan analisis kebijakan, studi ini mengevaluasi apakah pengelolaan sumber daya alam saat ini masih selaras dengan semangat ayat 3 sebesar-besar kemakmuran rakyat atau justru terjebak dalam kepentingan oligarki. Menggunakan kerangka teori Justice as Fairness dari John Rawls dan konsep Keadilan Sosial Pancasila, penelitian menemukan adanya paradoks antara regulasi yang menekankan efisiensi pasar pada Pasal 33 pasca-amandemen dengan cita-cita ekonomi kekeluargaan. Hasil analisis menunjukkan bahwa dominasi korporasi dalam penguasaan lahan serta aktivitas ekstraktivisme telah memicu deforestasi masif yang memperparah bencana ekologis, seperti banjir dan longsor di Sumatera. Hal ini mengindikasikan pelanggaran terhadap prinsip keadilan distributif, komutatif, dan legal, di mana beban kerusakan lingkungan ditanggung oleh kelompok masyarakat rentan sementara manfaat ekonomi terkonsentrasi pada segelintir elit. Kesimpulannya, Pasal 33 pasca-amandemen menguatkan kontrol negara melalui sentralisasi perizinan, memperluas dominasi korporasi, serta meningkatkan kerugian rakyat sehingga semakin menjauhkan implementasi Pasal 33 dari prinsip keadilan sosial yang substantif. Kata kunci: Ekstraktivisme, Keadilan Sosial, Pancasila, Pasal 33, teori justice.